2022
DOI: 10.24136/oc.2022.008
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the organizational commitment, subjective vitality and burnout effects on turnover intention in private universities

Abstract: Research background: Faculties of private universities are under immense working pressure, which causes stress and burnout. The job burnout triggers the psychological pressure, which increases the turnover intention.  Purpose of the article: The undertaken study aims to evaluate the scale of burnout with its three-element model, which affects faculty members of private universities of Pakistan. This research also aims to examine the mediating effect of organizational commitment (e.g., affective, normative &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 57 publications
4
37
0
2
Order By: Relevance
“…In that case, the new recorded response will differ from the previous one regarding the effectiveness of ads of that specific brand. It means human behavior constantly changes because of external factors and stimuli, making it very complex [12,90,91]. Neuromarketing is used to gauge neural activity to get inspiration while watching certain ads [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that case, the new recorded response will differ from the previous one regarding the effectiveness of ads of that specific brand. It means human behavior constantly changes because of external factors and stimuli, making it very complex [12,90,91]. Neuromarketing is used to gauge neural activity to get inspiration while watching certain ads [13].…”
Section: Discussionmentioning
confidence: 99%
“…As we know, that neural network (artificial intelligence) is successfully used in Google search engines, YouTube social media, and other online media [89], and results have coincided with the human brain [83,88,90]. Therefore, we can say that artificial intelligence (neural network) is an effective tool for predicting the human brain in social sciences [57,80,91]. This research is essential and has a uniqueness in that we successfully employed neural networks (artificial intelligence) in social science topics such as to predict the consumer buying behavior regarding the critical characteristics of an advertisement [85,[92][93][94], which can change the human behavior to establish the efficacy of advertisement of certain brands.…”
Section: Discussionmentioning
confidence: 99%
“…At times, this role becomes a source of competition and thus becomes more stressful than any other job. Therefore, it can be concluded that the pursuit of a long and successful career even in academia is challenging and arduous, making faculty members vulnerable to risks of compromised well-being [ 1 , 2 ], because faculty members within their role have several other responsibilities, like undertaking research, administrative tasks, winning external grant projects, and teaching the most important. It, coupled with working extra time for other administrative or research-related jobs, with no such significant salary increases, makes it even more challenging [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The manifestation of a social welfare structure depends on a network representing a definition of health, satisfaction with physical health conditions, and social interactions. Accordingly, three basic norms define the rule and law of positive emotions, which are found in the welfare system and its structure [ 1 ]. Workers’ lives are “One of the most prominent challenges posed to the leaders these days” [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation